DESIGN EFFICIENT CENTRALIZED PATIENT DATABASE SYSTEM FOR HEALTHY MONITORING OF DISEASE DIAGNOSIS IMPROVEMENT - Sachin A. Vyawhare; Dr. Shashi Bhushan; Dr. M. S. Kathane; Rajesh R. Raut; Sapna R.Tayde (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Rapid and reasonably priced e-healthcare data collecting and disease diagnosis are being progressively made possible by recent advancements in biotechnologies and high-performance computers. The accuracy of the model developed from the vast e-healthcare data is necessary for efficiency and dependability. Natural language processing (NLP) technology will be used by Health Bot to analyze and elaborate on the creation of an intelligent system that can support telemedicine services. The comprehensive, modular, and user-friendly platform called Health Bot seeks to enhance how patients interact with the healthcare system. The software can analyze and classify free text and voice input data to symptoms using NLP and speech recognition techniques. In order to anticipate the likelihood that a patient would develop a certain ailment and to alert the patient in the event of a disorder, free categorized data are utilized in the machine learning (ML) training process of the artificial intelligence (AI) models. • e Health Bot is operating as a virtual medical assistant to gather any data required for a medical interview, provide medical evaluations, schedule appointments with doctors, and monitor/record the patient's health.